New Insight into HIV-Related Psychological Distress: A Concept Analysis. (January 2023) - Ma, Haiqi; Bu, Mengru; Zhai, Huimin; Li, Bing; Xiong, Ling
Psychological distress is a frequently reported outcome measure in HIV research. However, because of its poor conceptualization, many studies only partially capture it because they focus solely on depression or anxiety based on symptoms. This study undertook a concept analysis of HIV-related psychological distress (HRPD) using Walker and Avant's method. The findings include HRPD's (a) attributes, including changes to emotional status, symptom burden, HIV disclosure distress and HIV-related stigma; (b) antecedents, including HIV-related stressors, cognitive appraisal of stressors and difficulty coping with the disease or treatment; and (c) consequences, including poor health outcomes and posttraumatic growth. Lazarus and Folkman's theory and the conservation of resources theory were adapted to further understand HRPD. This article provides insight into HRPD and increases the awareness of how to screen and assess HRPD at an early stage. The findings indicate the need to develop specific and rigorous measures and to provide appropriate interventions.